2021
DOI: 10.3389/fmicb.2021.632095
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Proteomic and Transcriptomic Analyses Reveal the Roles of Brucella Homolog of BAX Inhibitor 1 in Cell Division and Membrane Homeostasis of Brucella suis S2

Abstract: BAX inhibitor 1 (BI-1) is an evolutionarily conserved transmembrane protein first identified in a screening process for human proteins that suppress BAX-induced apoptosis in yeast cells. Eukaryotic BI-1 is a cytoprotective protein that suppresses cell death induced by multiple stimuli in eukaryotes. Brucella, the causative agent of brucellosis that threatens public health and animal husbandry, contains a conserved gene that encodes BI-1-like protein. To explore the role of the Brucella homolog of BI-1, BrBI, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…Mutant strains were confirmed by PCR using alr -qF and alr -qR primers. To obtain the complemented strain, we constructed an expression plasmid (pBBARpc) containing a Flag tag [ 3 ]. The full-length alr open reading frame was amplified using alr -F and alr -R primers, and the PCR product was cloned into the laboratory’s pre-existing pBBARpc vector to generate the recombinant pBBARpc- alr plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutant strains were confirmed by PCR using alr -qF and alr -qR primers. To obtain the complemented strain, we constructed an expression plasmid (pBBARpc) containing a Flag tag [ 3 ]. The full-length alr open reading frame was amplified using alr -F and alr -R primers, and the PCR product was cloned into the laboratory’s pre-existing pBBARpc vector to generate the recombinant pBBARpc- alr plasmid.…”
Section: Methodsmentioning
confidence: 99%
“…Brucella is a Gram-negative bacterium that grows extracellularly and which replicates within both phagocytic and non-phagocytic host cells [ 3 ]. Despite lacking many of the classical virulence factors that other pathogenic bacteria possess, including invasive proteases, exotoxins, capsules, and fimbriae, Brucella has evolved a remarkable ability to evade host immunity and cause chronic infection.…”
Section: Introductionmentioning
confidence: 99%
“…PI freely penetrates damaged cell membranes and binds to intracellular DNA, which leads to the emission of red fluorescence. Therefore, the fluorescence microscopy detection of PI staining within cells indirectly reflects changes in the Brucella cell membrane [14]. No red fluorescence was observed in wild-type, ∆alr, and C∆alr strains without PI treatment.…”
Section: Changes In Membrane Integrity Observed By Fluorescence Micro...mentioning
confidence: 99%
“…For antibiotic resistance testing, cultures were placed in a 96-well enzyme-linked immunosorbent assay (ELISA) plate (at 2 × 10 4 CFUs/well) and were exposed to polymyxin B at concentrations of 1200, 600, and 300 µg/mL or lincomycin at concentrations of 500, 375, and 250 µg/mL at 37 • C for 1 h. The cultures were tenfold diluted and plated onto TSA agar, followed by incubation at 37 • C for 3 days. The CFUs after antibiotic treatment were counted and compared to those of untreated cultures to calculate the survival rate for each sample [14].…”
Section: Brucella Stress Resistance Testsmentioning
confidence: 99%
“…Evidence supports that the virulence of Brucella is completely dependent on its ability to survive and replicate in host cells [9][10][11]. As a stealthy pathogen, Brucella has evolved numerous strategies to defend host bactericidal responses and then establish intracellular multiplication niches [12,13]. It has been reported that Brucella infection induces the premature death of neutrophils to promote their phagocytosis by macrophages [14,15].…”
Section: Introductionmentioning
confidence: 98%